TRANSFORMATION OF PONDOK PESANTREN IN INCREASING ISLAMIC EDUCATION IN JAMBI PROVINCE - Mukhtar Mukhtar; Ahmad Syukri; Abdullah Yunus (Yayasan Literasi Kita Indonesia, 2020)
This study has a background and purpose, namely to find out and analyze why Islamic Boarding School Transformation can Improve Islamic Religious Education in Jambi Province. The research methodology used is qualitative with data collection instruments with observation, interviews and documentation. The results of the study are the Transformation of Islamic Boarding Schools in Improving Islamic Education in Jambi Province (case study in the Sa'atuddaren Islamic boarding school in Jambi City, Al-Baqiyatush Shalihat Islamic boarding school in Tanjung Jabung Barat Regency and Nurul Jalal Islamic Boarding School in Tebo district), which is to make Islamic boarding schools are bigger, contribute to Islamic education, quality output, student who are able to continue their education outside the Province and Overseas (Egypt, Yemen, Medina), and achieve provincial and national level achievements. The achievements were in the field of Musawatbaqah Tilawatil Quran (MTQ), among others; champion of tahfidzul quran, fahmil quran, quran syarhil, quran recitations, quran qhatil, hadrah, promising nazom and natsar. Then the Muyabaqah Qiraatul Pole (MQK) field, among others; champion of interpretation, balaghah, fiqh, ushul fiqh, mantek, ma’ani. Key words: